Comparative Analysis of TOEFL Prediction Score Results and Students' Quizzes Score - Mila Karmilah (International Journal of Scientific Multidisciplinary Research, 2023)
The aim of this research was to investigate whether there is a difference between general English scores and Toefl Prediction scores. and Is the difference significant or not This research method used explanatory correlational. The analysis technique used  Annova variant and  Paired sample t test. The population of this study were students of Al Islam Polytechnic, Bandung, 1st semester Radiology study program. The results showed that there was no significant evidence to reject H0. and there is no significant difference between TOEFL prediction scores and middle test  quizzes scores